The Professionalism of Certified Teachers in Instructional Process: A Case Study of Secondary School Teachers in Jambi - Jailani, Muhammad Syahran (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
The purpose of this research is to reveal teaching commitment of certified teachers who teach in private Madrasah in Jambi to increase the learning. The participants are teachers (civil servant) who teach in several private Madrasah in Jambi. It is the phenomenology qualitative research, referring to the eleventh steps proposed by Spradley (1980). This research revealed two important findings. First, the teachers realize that they need to be committed in their teaching as a way to improve their professionalism and also instructional quality. The second important finding is that there is a lack of supervisory effort to supervise certified teachers, and thus there has no coordination between teachers and the stakeholders. This makes MGMP and KKG does not run effectively.